STRENGTHENING SOCIAL AND CULTURAL RESILIENCE OF INDONESIAN MIGRANT WORKERS IN SOUTH KOREA THROUGH A COMMUNITY-BASED APPROACH - Raharjo; Iwan Sugihartono; Etin Solihatin (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2025)
Abstract The resilience of Indonesian migrant workers (PMI) in South Korea has become an important issue, particularly in the context of social and cultural adaptation. Many workers face challenges such as language barriers, cultural differences in the workplace, limited access to information about labor rights, and a lack of social networks, which often lead to stress, discrimination, and vulnerability to exploitation. This community service program aimed to strengthen the social and cultural resilience of Indonesian migrant workers through a community-based approach. The activities included cultural adaptation training, legal literacy workshops on labor rights and obligations, the development of conflict management skills, and the establishment of solidarity-based migrant worker communities. The program was carried out in collaboration with the Embassy of the Republic of Indonesia in Seoul, the IMNIDA community, and supported by six Indonesian universities under the ALPTKNI consortium. The methods applied encompassed socialization, mentoring, and ongoing community engagement. The outcomes of the program indicated an increased awareness of labor rights, improved cultural adaptation skills, and stronger social solidarity among participants. Furthermore, the establishment of long-term partnerships with local organizations ensured the sustainability of the program. This initiative not only contributed to the protection and empowerment of Indonesian migrant workers in South Korea but also served as a replicable model for similar interventions in other destination countries. The program also aligned with the Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being) and SDG 17 (Partnerships for the Goals), highlighting the strategic role of higher education institutions in global community empowerment and cultural diplomacy. Keywords: Social and cultural resilience; Indonesian migrant workers; community empowerment; South Korea; labor rights; sustainability. Abstrak Ketahanan pekerja migran Indonesia (PMI) di Korea Selatan telah menjadi isu penting, terutama dalam konteks adaptasi sosial dan budaya. Banyak pekerja menghadapi tantangan seperti hambatan bahasa, perbedaan budaya di tempat kerja, keterbatasan akses terhadap informasi tentang hak-hak ketenagakerjaan, dan kurangnya jaringan sosial, yang sering kali menyebabkan stres, diskriminasi, dan kerentanan terhadap eksploitasi. Program pengabdian kepada masyarakat ini bertujuan untuk memperkuat ketahanan sosial dan budaya pekerja migran Indonesia melalui pendekatan berbasis komunitas. Kegiatan yang dilakukan mencakup pelatihan adaptasi budaya, lokakarya literasi hukum tentang hak dan kewajiban tenaga kerja, pengembangan keterampilan manajemen konflik, dan pembentukan komunitas pekerja migran berbasis solidaritas. Program ini dilaksanakan bekerja sama dengan Kedutaan Besar Republik Indonesia di Seoul, komunitas IMNIDA, dan didukung oleh enam universitas Indonesia di bawah konsorsium ALPTKNI. Metode yang diterapkan mencakup sosialisasi, pendampingan, dan keterlibatan komunitas yang berkelanjutan. Hasil dari program menunjukkan peningkatan kesadaran terhadap hak-hak tenaga kerja, peningkatan keterampilan adaptasi budaya, dan penguatan solidaritas sosial di antara para peserta. Selain itu, pembentukan kemitraan jangka panjang dengan organisasi lokal memastikan keberlanjutan program. Inisiatif ini tidak hanya berkontribusi terhadap perlindungan dan pemberdayaan pekerja migran Indonesia di Korea Selatan, tetapi juga berfungsi sebagai model yang dapat direplikasi untuk intervensi serupa di negara tujuan lainnya. Program ini juga sejalan dengan Tujuan Pembangunan Berkelanjutan (SDGs), khususnya SDG 3 (Kehidupan Sehat dan Sejahtera) dan SDG 17 (Kemitraan untuk Mencapai Tujuan), yang menyoroti peran strategis lembaga pendidikan tinggi dalam pemberdayaan masyarakat global dan diplomasi budaya. Kata kunci: Ketahanan sosial dan budaya; pekerja migran Indonesia; pemberdayaan komunitas; Korea Selatan; hak-hak ketenagakerjaan; keberlanjutan